Peningkatan Produktivitas Peternak Kambing Melalui Inovasi Pakan Fermentasi dan Manajemen Kesehatan Ternak pada KUB Berkah Lestari - Jenal Sodikin; Unggul Satria Jati; Ari Kristiningsih; Khoeruddin Wittriansyah (Madani : Indonesian Journal of Civil Society, 2026)
Livestock management has a strategic role in Indonesia, especially in goat farming, which is widely developed by local communities. However, the livestock feed currently used is still not processed effectively because it mainly consists of fresh green grass and is highly dependent on seasonal conditions. This situation can affect animal growth and the quality of goat production. Therefore, innovation in feed processing and improvement of product quality management are urgently needed. The purpose of this community service program is to implement fermented feed innovation and provide training on livestock health management for farmer groups. The implementation method includes counseling, training, demonstration of fermented feed production, training on sanitation and animal health management, and monitoring for six weeks. The program results show an increase in livestock weight by 19.1%, a reduction in feed costs by 24.1%, an improvement in feed conversion efficiency (FCR) by 21%, and an increase in farmers’ income by 29.2%. This program has proven to be effective in improving livestock productivity and supporting the sustainable welfare of farmers.